Poznań Maraton - badanie jakości imprezy sportowej metodą teamqual - Waśkowski, Zygmunt (Poznan Marathon - Research of Sports Event Quality by Teamqual Method, 2006)
Competition on Polish sport market forces marketing orientation from sport organizations. Marketing activity is absolutely necessary to organize an effective marathon ran. Using Teamqual method to research quality of Poznan Marathon - the biggest ran in Poland - proved that runners are satisfied in 96%. 150 runners (started 3000) judged five elements of quality "ideal" marathon and Poznan Marathon. In four instances the expectations are almost fulfilled, but in one instance - additional services - the expectations are fulfilled even over 100%.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 592-596